Structural and pharmacological analysis of O-2050, a putative neutral cannabinoid CB(1) receptor antagonist - Wiley, Jenny L. (2011)
Rimonabant, the prototypic antagonist of cannabinoid CB(1) receptors, has been reported to have inverse agonist properties at higher concentrations, which may complicate its use as a tool for mechanistic evaluation of cannabinoid pharmacology. Consequently, recent synthesis efforts have concentrated on discovery of a neutral antagonist using a variety of structural templates. The purpose of this study was to evaluate the pharmacological properties of the putative neutral cannabinoid CB(1) receptor antagonist O-2050, a sulfonamide side chain analog of Δ(8)-tetrahydrocannabinol. O-2050 and related sulfonamide cannabinoids exhibited good affinity for both cannabinoid CB(1) and CB(2) receptors. While the other sulfonamide analogs produced cannabinoid agonist effects in vivo (e.g., activity suppression, antinociception, and hypothermia), O-2050 stimulated activity and was inactive in the other two tests. O-2050 also decreased food intake in mice, an effect that was reminiscent of that produced by rimonabant. Unlike rimonabant, however, O-2050 did not block the effects of cannabinoid agonists in vivo, even when administered i.c.v. In contrast, O-2050 antagonized the in vitro effects of cannabinoid agonists in [(35)S]GTPγS and mouse vas deferens assays without having activity on its own in either assay. Further evaluation revealed that O-2050 fully and dose-dependently substituted for Δ(9)-tetrahydrocannabinol in a mouse drug discrimination procedure (a cannabinoid agonist effect) and that it inhibited forskolin-stimulated cyclic AMP signaling with a maximum efficacy of approximately half that of the full agonist CP55,940 [(−)-cis-3-[2-hydroxy-4(1,1-dimethyl-heptyl)phenyl]-trans-4-(3-hydroxy-propyl)cyclohexanol]. Together, these results suggest that O-2050 is not a viable candidate for classification as a neutral cannabinoid CB(1) receptor antagonist.